2019
DOI: 10.1155/2019/8041767
|View full text |Cite
|
Sign up to set email alerts
|

Shear Lag Effects in Angles Welded at Both Legs

Abstract: The shear lag phenomenon is known to reduce the tensile capacity of tension members. There are various parameters affecting shear lag that have not been considered before. In addition, previous studies have been conducted mainly on single steel sections. Using numerical methods, the present study investigates the effects of relevant parameters on shear lag in single- and double-angle sections welded at both legs. The studied parameters are connection eccentricity, connection length, gusset plate thickness, mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Moreover, since configuration of the suggested connection in this study is similar to double angle sections connected at both legs (Figure 13), the results of this study were compared to the shear lag coefficient of double angle connections studied by Abedin et al [7]. Table 5 shows the comparison of shear lag coefficients for two similar RHS and double angle connections with same leg sizes and connection lengths.…”
Section: Figure 11 the Proposed Equation For The Rhs Connections Conmentioning
confidence: 85%
See 1 more Smart Citation
“…Moreover, since configuration of the suggested connection in this study is similar to double angle sections connected at both legs (Figure 13), the results of this study were compared to the shear lag coefficient of double angle connections studied by Abedin et al [7]. Table 5 shows the comparison of shear lag coefficients for two similar RHS and double angle connections with same leg sizes and connection lengths.…”
Section: Figure 11 the Proposed Equation For The Rhs Connections Conmentioning
confidence: 85%
“…The experimental results revealed that thickness of cap plates has a negligible effect on the ultimate joint capacity. Abedin et al [7,8] studied tension behaviour of single and double angle connections. The results of the numerical analyses showed that, in single angle connections, the effects of connection length, connection eccentricity, and gusset plate thickness are more pronounced, while in double-angle connections the last parameter is not very critical.…”
Section: Introductionmentioning
confidence: 99%
“…Limited studies have also been performed on the connection details of cross-frames [27] and the effect of lateral bracing and buckling of main girders after a fracture. Four types of cross-frame connection details, including the use of end-plate connection, connection plate and split-tee connection were experimentally investigated by Takahashi et al [28].…”
Section: Of 14mentioning
confidence: 99%
“…If (37) be divided by positive term 1 n   , the link's flow will be obtained as it shown in the next term. (38) Since the link's flow can never be negative, the former term and consequently (28) will never hold. As a result, just when the following inequalities hold, DNDP's result in fix and variable demand conditions differs.…”
Section:  mentioning
confidence: 99%